When Paywall Goes AWOL: The Demand for Open Access Education Research - Seth Gershenson; Morgan S. Polikoff; Rui Wang (Institute of Labor Economics (IZA), 2019)
As universities cut library funding and forego expensive journal subscriptions, many academic organizations and researchers, including the American Educational Research Association (AERA), are moving towards open-access publications that are freely downloadable by anyone with a working internet connection. However, the impact of paywalls on the consumption of academic articles is unclear. We provide novel evidence on this question by exploiting a natural experiment in which six high-impact, usually gated AERA journals became open access for a two-month period in 2017. Using monthly download data, and an always-open access journal as a control group, we show that making journals open access increased article downloads in those journals by 60 to 80% per month. Given a per-article download price of 36, this suggests a download elasticity of about 0.3 to 0.4.
Keywords: L17; O33; 330; open access; academic journal